CT-guided percutaneous radiofrequency ablation in osteoid osteoma: re-assessments of results with optimized technique and possible pain patterns in mid-term follow-up - Omlor, Georg; Merle, Christian; Lehner, Burkhard; Ewerbeck, Volker; Rehnitz, Christoph; Weber, Marc-André (RöFo, 2012)
To re-assess radiofrequency ablation (RFA) of osteoid osteoma (OO) with an optimized technique and to evaluate patterns of post-interventional pain important for the detection of recurrence.
Gesehen am 27.08.2018